Cartografia das prevalências de internações de idosos hipertensos e diabéticos e índice de desenvolvimento humano no Brasil - Sousa, Erika Epaminondas de (2018)
The accelerated growth of the elderly population is a worldwide reality, becoming a major challenge for contemporary public health. The global increase in population aging poses greater challenges on health systems and services for the elderly. This population group is in epidemiological and demographic evidence, becoming a priority in studies and interventions in health, particularly in Brazil. In this context, one approach to measuring the quality and availability of health care for the elderly is to assess hospital admission rates, as they are treated early and appropriately to avoid hospitalization. The main objective of this research is to analyze the prevalence of systemic arterial hypertension and type 2 diabetes mellitus and human development index in the hospital network in the elderly in Brazil. This is an aggregate, quantitative and qualitative, ecological time-series study on the distribution of prevalence coefficients of Systemic Arterial Hypertension and Type 2 Diabetes Mellitus from 534,691 cases of hospitalizations in the 27 Brazilian states, years of 2010 and 2016. The data were notified by year and by place of residence being obtained from the Hospital Information System of the database of the Unified Health System. Statistical analyzes were done using the statistical program R, using the coefficient of prevalence of diseases in each state and region, allowing a visualization of the spatial pattern of these morbidities using the k-means clustering method. The spatial distribution of these patterns was explored, and a multiple regression model was developed to estimate the relationship between prevalence indicators and sociodemographic variables (per capita income, illiteracy rate, and human development index). In the present study, the relationship between the prevalence of hospitalization for systemic arterial hypertension and the human development index (95% CI = -5.4%, -2.6% and -4.040% and p = 0.000) was observed; and prevalence of hospitalization for Diabetes Mellitus and Human Development Index (95% CI = -4.8%, -1.7% and coefficient -3.293% and p = 0.000), as well as a relation between the prevalence of hospitalization for Arterial Hypertension and income (95% CI = -1.7%, -0.3% and coefficient 0.773% and p = 0.000) and the relationship between the prevalence of hospitalization for diabetes mellitus and the rate of illiteracy (95% CI = 0.0; 0,5%, coefficient 0.278% and p = 0.039) in the multiple regression model with panel data. We conclude that there was a trend towards stabilization and reduction in the prevalence of hospitalizations for Hypertension and Diabetes Mellitus in most states and in different Brazilian regions, higher prevalences of hospitalization in males, and in the higher age range. It should be noted that a negative relationship between the Human Development Index and the prevalence of hospitalizations for both chronic noncommunicable diseases was identified. Although treatment and control of Hypertension and Diabetes improved, the values of these variables remained at high levels.